Deconstructing the Teaching Campus Program under the MBKM Policy: A Study of the PPKn Program at Faculty of Social Sciences and Law, Makassar State University - Imam Suyitno (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: This study examines the policy transformation introduced through the Kampus Mengajar program, which signifies a reorientation and restructuring of student involvement in learning activities within educational units. The program reflects a deconstruction of earlier policy frameworks by broadening opportunities for experiential learning beyond classroom settings. Universitas Negeri Makassar, as a major teacher‐training institution (LPTK) in Eastern Indonesia, has participated in this initiative since its initial implementation through the PPKn study program. Objectives: This research aims to: (1) describe the construction of teaching campus practices in educational units based on curriculum provisions applied in the PPKn FIS-H UNM study program; (2) map the deconstruction process of the teaching campus policy within the program; and (3) analyze the mechanism of course recognition granted to students participating in Kampus Mengajar activities. Methods: The study applies a descriptive qualitative approach involving key informants, namely the head of the PPKn study program, the vice dean for academic affairs, and lecturers responsible for course recognition. Data collection was conducted through interviews and documentation, while data analysis followed the stages of data condensation, data display, and conclusion drawing. Source triangulation was used to validate data credibility. Results: The findings indicate that student involvement was previously implemented through PLP2 or integrated KKN-PLP activities, whereas the restructured policy positions Kampus Mengajar as a one-semester activity available in semesters five to seven, with course recognition equivalent to 20 credits. Conclusion: The new policy facilitates accelerated study completion while simultaneously raising concerns regarding its potential implications for developing the professional competencies of future PPKn teachers.